The re-creation of the Spanish Civil War in recent Irish historical fiction - Lázaro, Alberto (ELOPE (Ljubljana), 2025)
The Spanish Civil War (1936–1939) captured worldwide interest, generating a wealth of literature across multiple genres. In Ireland, this conflict sparked fervent debate, reflecting the nation’s own history of civil strife, with Irish volunteers joining both sides of the Spanish conflict. While conventional narratives often oversimplify the war as a clash of opposing ideologies, certain authors endeavour to offer nuanced portrayals that transcend binary interpretations. Drawing upon Kate McLoughlin’s insights into war representation, as delineated in Authoring War (2011),and Laura Saxton’s exploration of “accuracy” and “authenticity” in historical fiction, this article analyses three recent Irish historical novels –Dermot Bolger’s The Family on Paradise Pier (2005), Maurice Leitch’s Gone to Earth (2019), and Anamaría Crowe Serrano’s In the Dark (2021) – to explore how they re-create the complexities of the Spanish Civil War, examining their thematic depth, historical accuracy and narrative authenticity.
Keywords: Anamaría Crowe Serrano; Dermot Bolger; historical fiction; Maurice Leitch; Spanish Civil War; španska državljanska vojna; zgodovinski roman